Analysis of hotz plate appliance to the development of maxillary arch growth of patient with cleft lip and palate - Edy Machmud (Journal of Dentomaxillofacial Science, 2007)
This study was an observational, cross sectional study with purpose toanalyze the effect of hotz plate appliance to the development ofmaxillary arch of patients with cleft lip and palate. Twelve sampleswith cleft lip andpalate, age under 2 years were recruitedfrom twodifferent hospitals. Six samples used hotz plate appliance wererecruited from Rumah Sakit Hasan Sadikin, Bandung while the othersix as control didn't use hotz plate appliance were recruited fromRumah Sakit Haji, Makassar. The result showed that minor maxillaryarch was similar in size with major maxillary arch of patient with hotzplate appliance, however, patient without hotz plate appliance,showed longer minor maxillary arch than major maxillary arch. It canbe concluded from this study that hotz plate appliance had an effecton the palatal development of patient with complete unilateral cleft lipand palate and also prevented the collapse of minor maxillary arch toeither anterolateral or anteromedial.